Sistem Pakan Ikan Berbasis Internet of Things Pada Jurusan Vokasional - Setyoko; Nur Rohmani, Mayda; Pramono (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
The fisheries industry continues to evolve, requiring innovative approaches to enhance production efficiency. Fish feeding management is a key aspect of cultivation that requires careful supervision and control. In this context, the use of Internet of Things (IoT) technology promises intelligent solutions that can efficiently monitor and control fish feeding. This research aims to design and implement an IoT-based Fish Feeding System at the Vocational Fisheries Department. Using qualitative methods involving surveys and direct observations, we developed a system consisting of integrated architecture with main components and appropriate control algorithms. With the adoption of IoT technology, fish feeding management can become more automated and measurable, improving feed efficiency and reducing waste. The implementation of this system also makes a positive contribution to vocational education in fisheries, providing practical experience to students. The results of this research indicate that the IoT-based Fish Feeding System has great potential to enhance fisheries production efficiency and provide an innovative approach to fish feeding management that can be widely adopted by the fisheries industry.